Resin-reinforced glass ionomer cement composition for dental adhesion having excellent adhesiveness and residual cement removal

By adopting a specific composition of resin-reinforced glass ionomer watermarinate composition for dental bonding, the problem of difficulty in removing residual watermarinate in the prior art is solved, and a long-term semi-cured state and difficult to tear are achieved, and the adhesion and safety of the dental patching device are improved.

CN119700553APending Publication Date: 2025-03-28SHOFU INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411361646.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing resin-reinforced glass ionomer watersides for dental bonding are insufficient to maintain a semi-cured state during the curing process, which makes it difficult to remove the remaining watersides, especially when adjacent surfaces between the teeth.

Method used

A resin-reinforced glass ionomer watermantin composition for dental bonding consisting of a first and a second dose is used, wherein the first dose comprises an acid-reactive glass powder and an aryl borate compound, the second dose comprises polyoleic acid and water, and a polymerizable monomer is added to at least one, and the ratio of polyoleic acid and water is adjusted to optimize adhesion and removal.

Benefits of technology

It is achieved to maintain a semi-cured state suitable for removing the remaining watermenite during the curing process, and to have difficult to tear when the remaining watermenite is thin, reducing the risk of periodontitis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065079680000041
    Figure BDA0005065079680000041
  • Figure BDA0005065079680000251
    Figure BDA0005065079680000251
  • Figure BDA0005065079680000261
    Figure BDA0005065079680000261
Patent Text Reader

Abstract

Provided is a resin-reinforced glass ionomer cement composition for dental adhesion, which is capable of maintaining a semi-cured state, which is the timing at which the remaining cement is removed, for a longer period of time, is difficult to tear when the remaining cement is thin, and has excellent adhesion to dentine, which is important as the basic characteristics of dental cement. A resin-reinforced glass ionomer cement composition for dental adhesion, which is composed of a first agent comprising (a) an arylborate compound and (b) an acid-reactive glass powder and a second agent comprising (c) a polyolefin acid and (d) water, and which contains (e) a polymerizable monomer in at least one of the first agent and the second agent, wherein the content of the (c) polyolefine acid contained in the second agent is in the range of more than 20 mass% and less than 70 mass% with respect to the total amount of the second agent, and the content of the (c) polyolefine acid contained in the second agent and the content of the (d) water contained in the second agent are in the range of more than 20 mass% and less than 70 mass% with respect to the total amount of 100 parts by mass of the (c) polyolefine acid contained in the second agent and the (d) water contained in the second agent. The content of the (c) polyenoic acid contained in the second agent is in the range of more than 45 parts by mass and less than 75 parts by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dental adhesive resin-reinforced glass ionomer cement composition useful as a dental cement for bonding and / or adhering a dental prosthetic device to a tooth. Background Art

[0002] In dental clinics, dental cements are used as materials for bonding and / or adhering dental prostheses such as crowns, inlays, and bridges to teeth that have been partially damaged in shape due to caries or fractures. Currently, the main dental cements used include adhesive resin cements, adhesive glass ionomer cements, and adhesive resin-reinforced glass ionomer cements. As the most important basic property, these dental cements are required to have adhesion to tooth structure. Furthermore, the coating thickness (the thickness of the cement layer between the tooth and the dental prostheses) is also required to be thin so that the floating of the dental prostheses is minimized when applied to the teeth.

[0003] Among them, the adhesive resin reinforced glass ionomer cement contains the main components of the adhesive resin cement and the adhesive glass ionomer cement, and is a useful material that has both the high mechanical properties of the former and the properties of the latter such as strengthening of the tooth texture by the slow release of fluoride. For example, in Japanese Patent Publication No. 2014-181190, a powder-liquid dental resin reinforced glass ionomer cement composed of a powder material and a liquid material and further containing a chemical polymerization initiator in the powder material and / or the liquid material is disclosed, which has excellent adhesion to the tooth texture and storage stability, and is useful for the bonding of fillings, repairs, and prostheses, wherein the powder material contains aluminum fluorosilicate glass particles and polyolefinic acid powder in a specific ratio, and the liquid material contains a polymerizable monomer having an acidic group, a polymerizable monomer not having an acidic group, a specific alkaline compound, and water, and exhibits a pH in a specific range.

[0004] The operation of installing a dental prosthesis on a tooth using the dental adhesive resin reinforced glass ionomer cement is performed by applying a cement kneaded substance to the bonding surface of the dental prosthesis and then crimping the dental prosthesis to the tooth. At this time, the kneaded substance is applied in excess of the required amount so that the kneaded substance is spread over the entire bonding interface between the dental prosthesis and the tooth. Therefore, when the dental prosthesis is crimped to the tooth, the remaining kneaded substance overflows from the bonding portion between the dental prosthesis and the tooth. The remaining kneaded substance that overflows is called residual cement, and is removed using a sharp-tipped instrument called a dental probe when the curing is performed to a certain extent and reaches a semi-cured state.

[0005] In addition, if the dental prosthesis is a crown or a bridge, the bonding portion between the dental prosthesis and the tooth (hereinafter referred to as the edge portion) is located near or below the gum edge on the surface of the tooth. Therefore, when removing the remaining cement, great care must be taken to avoid damaging the surrounding gums with a dental probe.

[0006] In particular, if it is the adjacent surface between teeth, the removal of the excess cement becomes a more difficult task. Therefore, in addition to the above-mentioned basic properties (adhesion to tooth structure, thin film thickness) for dental resin-reinforced glass ionomer cement, it is also required to be able to easily remove the excess cement.

[0007] If the removal of the remaining cement is insufficient, the risk of periodontitis may increase (Thomas G. Wilson Jr., J Periodontol 2009, 80(9), 1388-1392). As such, the removability of the remaining cement has a great influence on the prognosis and is therefore an extremely important property. Summary of the invention

[0008] As described above, the removal of the remaining cement is performed when it becomes a semi-cured state. This is because the remaining cement can be easily removed without strong force, and the risk of residue and damage to the gums is suppressed to a minimum. Therefore, during the curing process of the remaining cement, the longer the semi-cured state is, the more room there is for the removal operation, so it is preferred. In addition, if the remaining cement in the semi-cured state has the property of being difficult to tear, the remaining cement can be removed in one piece, which significantly reduces the burden of the operation, so it is more preferred. This property of being difficult to tear is particularly useful when removing the remaining cement from adjacent surfaces where the visual recognition is poor and the risk of residual cement remaining is high.

[0009] Conventional resin-reinforced glass ionomer cement for bonding maintains a semi-cured state for a certain period of time during the curing process, but the semi-cured state is not sufficient for cases where the removal of the remaining cement of multiple teeth at once takes a long time. In addition, when the thickness of the remaining cement is thin, it may tear during removal, and a property that is more difficult to tear is required.

[0010] Therefore, an object of the present invention is to provide a resin-reinforced glass ionomer cement composition for dental bonding, which can maintain a semi-cured state for a longer period of time at the time when the remaining cement is removed, is difficult to tear even when the remaining cement is thin, and has excellent adhesion to tooth structure, which is an important basic property of dental cement.

[0011] The present inventors have conducted intensive studies in view of the above-mentioned problems, and as a result, have found that a resin-reinforced glass ionomer cement composition for dental bonding, which is composed of a first agent and a second agent, wherein the first agent contains an acid-reactive glass, and the second agent contains a polyolefinic acid and water, and at least one of the first agent and the second agent contains a polymerizable monomer, wherein the first agent contains an aryl borate compound as a polymerization initiator, and the content of the polyolefinic acid in the second agent and the ratio of the polyolefinic acid contained in the second agent to water are set to specific ranges, can solve the above-mentioned problems, and have thus completed the present invention.

[0012] That is, the above-mentioned problems are solved by the following component configuration.

[0013] A resin-reinforced glass ionomer cement composition for dental bonding, which is composed of a first agent and a second agent, and at least one of the first agent and the second agent contains (e) a polymerizable monomer, wherein the first agent contains (a) an aromatic borate compound and (b) an acid-reactive glass powder, and the second agent contains (c) a polyolefinic acid and (d) water, characterized in that the content of the polyolefinic acid (c) contained in the second agent is in the range of greater than 20 mass % and less than 70 mass % relative to the total amount of the second agent, and when the total amount of the polyolefinic acid (c) contained in the second agent and the water (d) contained in the second agent is set to 100 mass %, the content of the polyolefinic acid (c) contained in the second agent is in the range of greater than 45 mass % and less than 75 mass %.

[0014] The dental adhesive resin-reinforced glass ionomer cement composition of the present invention exhibits excellent adhesion to tooth structure, and maintains a semi-cured state suitable for removing excess cement for a long time during the curing process, so that the excess cement can be removed with ease. Furthermore, even when the thickness of the excess cement is reduced, it has the property of being difficult to tear, so the excess cement can be easily removed from adjacent surfaces between teeth, which are difficult to remove. As a result, the risk of periodontitis caused by residual excess cement is reduced. DETAILED DESCRIPTION

[0015] In the present specification, "polyalkenoic acid" refers to a polymer including an ethylenically unsaturated monomer unit having an acidic group.

[0016] In the present specification, (meth)acrylate is used to collectively describe both acrylate and methacrylate, (meth)acryloyl is used to collectively describe both acryloyl and methacryloyl, and (meth)acrylamide is used to collectively describe both acrylamide and methacrylamide.

[0017] The present invention provides a dental adhesive resin-reinforced glass ionomer cement composition, which is composed of a first agent and a second agent, and at least one of the first agent and the second agent contains (e) a polymerizable monomer, wherein the first agent contains (a) an aromatic borate compound and (b) an acid-reactive glass powder, and the second agent contains (c) a polyolefinic acid and (d) water, characterized in that the content of the polyolefinic acid (c) contained in the second agent is in a range of greater than 20 mass % and less than 70 mass % relative to the total amount of the second agent, and the content of the polyolefinic acid (c) contained in the second agent is in a range of greater than 45 mass parts and less than 75 mass parts in 100 mass parts of the total amount of the polyolefinic acid (c) contained in the second agent and the water (d) contained in the second agent.

[0018] By setting it as this component structure, excellent adhesion to tooth structure is exhibited, and a semi-cured state suitable for removing excess cement is maintained for a long time during the curing process. In addition, the excess cement in the semi-cured state has the property of being difficult to tear, so the excess cement can be easily removed from the edge.

[0019] The present invention will be described in detail below. The (a) aryl borate compound that can be used in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention is an organic boron compound having three or four aromatic groups in one molecule and represented by the following general formula (1).

[0020] [Formula (1)]

[0021]

[0022] [In the formula, R1 represents an alkyl group which may be substituted, an aryl group which may be substituted, or an alkenyl group which may be substituted, and R2 to R7 independently represent a hydrogen atom, a halogen atom, a nitro group, or an alkyl group which may be substituted, a phenyl group which may be substituted, or an alkoxy group which may be substituted. In addition, L + represents an alkali metal ion, a tertiary ammonium ion or a quaternary ammonium ion, a quaternary pyridinium ion, a quaternary quinolinium ion or a quaternary phosphonium ion.]

[0023] Hereinafter, (a) the aryl borate compound represented by the above formula (1) will be specifically exemplified.

[0024] Examples of the borate compound having three aromatic groups in one molecule include monoalkyltriphenylborane, monoalkyltri(p-chlorophenyl)borane, monoalkyltri(p-fluorophenyl)borane, monoalkyltri[3,5-bis(trifluoromethyl)phenyl]borane, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borane, monoalkyltri(p-nitrophenyl)borane, monoalkyltri(m-nitrophenyl)borane, monoalkyltri(p-butylphenyl)borane, monoalkyltri(m-butylphenyl)borane, and monoalkyltri(m-butylphenyl)borane. ) boron, monoalkyltri(p-butoxyphenyl)boron, monoalkyltri(m-butoxyphenyl)boron, monoalkyltri(p-octyloxyphenyl)boron, monoalkyltri(m-octyloxyphenyl)boron (alkyl group is n-butyl, n-octyl, n-dodecyl, etc.), sodium salt, lithium salt, potassium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, tributylamine salt, triethanolamine salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt, butylquinolinium salt, etc., but are not limited to these.

[0025] Examples of borate compounds having four aromatic groups in one molecule include tetraphenylboron, tetra(p-chlorophenyl)boron, tetra(p-fluorophenyl)boron, tetra(3,5-bis(trifluoromethyl)phenyl)boron, tetra(3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl)boron, tetra(p-nitrophenyl)boron, tetra(m-nitrophenyl)boron, tetra(p-butylphenyl)boron, tetra(m-butyl) The invention also includes sodium salts, lithium salts, potassium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, tributylamine salts, triethanolamine salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, butylquinolinium salts, etc. of tetra(p-butoxyphenyl)boron, tetra(m-butoxyphenyl)boron, tetra(p-octyloxyphenyl)boron, and tetra(m-octyloxyphenyl)boron, but is not limited to these.

[0026] These (a) aryl borate compounds may be used alone or in combination of plural kinds. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not contain aryl borate compounds other than the organic boron compound having three or four aromatic groups in one molecule.

[0027] The (a) aryl borate compound preferably contains 0.01% by mass or more and 30% by mass or less, and more preferably contains 0.1% by mass or more and 25% by mass or less, relative to the total amount of the (e) polymerizable monomer. If the content of the (a) aryl borate compound is less than 0.01% by mass, the curability may be deteriorated and the mechanical properties may be reduced. In addition, if the content of the (a) aryl borate compound is greater than 30% by mass, the storage stability may be deteriorated.

[0028] The (b) acid-reactive glass powder that can be used in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention needs to contain acid-reactive elements such as metal elements and fluorine elements. The (b) acid-reactive glass powder contains acid-reactive elements, so that it can undergo an acid-base reaction with the acidic group possessed by the (c) polyolefin acid in the presence of (d) water. Specifically, examples of acid-reactive elements include sodium, potassium, calcium, strontium, barium, lanthanum, aluminum, zinc, etc., but are not limited to these. These acid-reactive elements can contain one or more, and their content is not particularly limited.

[0029] Furthermore, in order to impart X-ray contrast properties to the dental adhesive resin-reinforced glass ionomer cement composition of the present invention, it is preferred that the (b) acid-reactive glass powder contains an X-ray opaque element. Specific examples of X-ray opaque elements include strontium, lanthanum, zirconium, titanium, yttrium, ytterbium, tantalum, tin, tellurium, tungsten, and bismuth, but are not limited thereto. In addition, there are no particular limitations on other elements contained in the (b) acid-reactive glass powder, and the (b) acid-reactive glass powder of the present invention can contain various elements.

[0030] Examples of (b) acid-reactive glass powder include, but are not limited to, aluminosilicate glass, borosilicate glass, aluminoborate glass, boroaluminosilicate glass, phosphate glass, boric acid glass and silica glass containing the acid-reactive elements shown above, fluorine and an X-ray non-transparent element.

[0031] Furthermore, the particle shape of the (b) acid-reactive glass powder is not particularly limited, and any particle shape such as spherical, needle-shaped, plate-shaped, crushed, or flaky can be used without any limitation. These (b) acid-reactive glass powders can be used alone or in combination of plural types.

[0032] The method for producing the (b) acid-reactive glass powder is not particularly limited, and any of the production methods such as melting, gas phase, and sol-gel can be used. Among them, the (b) acid-reactive glass powder produced by the melting method or sol-gel method, which can easily control the type of elements or their content, is preferably used.

[0033] (b) Acid-reactive glass powder can be crushed into a desired particle size for use. The crushing method is not particularly limited, and a material crushed by any crushing method in a wet method or a dry method can be used. Specifically, a high-speed rotary mill such as a hammer crusher, a turbine grinder, a ball mill, a planetary grinder, a container-driven mill such as a vibration mill, a clay dry pulverizer (Atritor), a media stirring mill such as a bead mill, or a jet mill can be used for crushing, and the particle size is appropriately adjusted according to the desired characteristics given to the dental adhesive resin reinforced glass ionomer cement composition of the present invention.

[0034] In the dental adhesive resin-reinforced glass ionomer cement composition of the present invention, in order to achieve a thin coating thickness, the 50% particle size (D50) of the (b) acid-reactive glass powder is preferably 0.1 μm or more and 30 μm or less, and more preferably 0.1 μm or more and 10 μm or less. Here, the "50% particle size (D50)" refers to the particle size when the cumulative value from the small particle size side is 50% in the volume-based particle size distribution measured using a laser diffraction scattering particle size distribution measuring device or the like.

[0035] If the 50% particle size (D50) of the (b) acid-reactive glass powder is less than 0.1 μm, its surface area increases and cannot be included in a large amount in the composition, so that the mechanical properties are sometimes reduced or the operating margin time is shortened. In addition, if the 50% particle size (D50) of the (b) acid-reactive glass powder is greater than 30 μm, the coating thickness becomes thicker, and the bonded and / or adhered dental prosthetic device floats, sometimes causing discomfort in the meshing. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention can contain only an acid-reactive glass powder having a particle size (D50) of 0.1 μm or more and 30 μm or less as the (b) acid-reactive glass powder.

[0036] (b) Acid-reactive glass powder can be subjected to various surface treatments, heat treatments, or agglomeration treatments in liquid phase, gas phase, etc., within a range that does not adversely affect the acid-base reaction with (c) polyolefin acid, so as to adjust the operability, curing characteristics, mechanical properties, etc. of the dental adhesive resin reinforced glass ionomer cement composition of the present invention. In addition, these treatments can be carried out alone or in a plurality of combinations, and the order in which each treatment is carried out is not particularly limited. Among them, surface treatment or heat treatment is preferred from the perspective of easy control of various characteristics and excellent productivity.

[0037] Specifically, the surface treatment of (b) acid-reactive glass powder can be exemplified by washing with an acid such as phosphoric acid or acetic acid, surface treatment with an acidic compound such as tartaric acid or polycarboxylic acid, surface treatment with a fluoride such as aluminum fluoride, surface treatment with silane compounds such as (meth)acryloyloxymethyltrimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, partially hydrolyzed oligomers of tetramethoxysilane, and partially hydrolyzed oligomers of tetraethoxysilane. The surface treatment that can be used in the present invention is not limited to the above-mentioned treatments, and these surface treatments can be used separately or in combination. Further, the amount of the surface treatment agent relative to (b) acid-reactive glass powder during surface treatment is not particularly limited, as long as it is appropriately adjusted according to the particle size and desired properties of the (b) acid-reactive glass powder.

[0038] Specifically, for example (b) heat treatment of the acid-reactive glass powder, a treatment method of heating the powder at a temperature of 200° C. to 800° C. for 1 hour to 72 hours using an electric furnace or the like can be cited. The heat treatment that can be used in the present invention is not limited to the above treatment, and the treatment process can also be a treatment under a single temperature condition or a multi-stage treatment under multiple temperature conditions.

[0039] The (b) acid-reactive glass powder preferably contains 30% by mass or more and 75% by mass or less, and more preferably contains 32% by mass or more and 73% by mass or less, relative to the total amount of the dental adhesive resin-reinforced glass ionomer cement composition of the present invention. If the content of the (b) acid-reactive glass powder is less than 30% by mass, the curing may be slow or the mechanical properties may be reduced. In addition, if the content of the (b) acid-reactive glass powder is greater than 75% by mass, the kneaded product may become too hard, the coating thickness may become thick, and the bonded and / or adhered dental prosthetic device may float, which may sometimes cause discomfort in the meshing.

[0040] The (c) polyolefinic acid that can be used in the dental adhesive resin reinforced glass ionomer cement composition of the present invention can be used without any restrictions as long as it is a homopolymer or copolymer of an olefinic unsaturated monomer having at least one acidic group such as a carboxyl group, a phosphoric acid group, a phosphonic acid group, a sulfonic acid group, etc. in the molecule, such as an olefinic unsaturated monocarboxylic acid, an olefinic unsaturated dicarboxylic acid, an olefinic unsaturated tricarboxylic acid, an olefinic unsaturated phosphoric acid, an olefinic unsaturated phosphonic acid, an olefinic unsaturated sulfonic acid. Furthermore, there is no problem even if the (c) polyolefinic acid is a copolymer of an olefinic unsaturated monomer having no acidic group in the molecule and an olefinic unsaturated monomer having an acidic group. Among them, since it is easy to obtain good adhesion to tooth structure and high mechanical properties, the acidic group possessed by the (c) polyolefinic acid is more preferably a carboxyl group. It should be noted that in this specification, "the acidic group possessed by the (c) polyolefinic acid is a carboxyl group" means that more than 60%, preferably more than 70%, and more preferably more than 80% of the acidic groups possessed by the (c) polyolefinic acid are carboxyl groups. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain only the (c) polyalkenoic acid whose acidic group is a carboxyl group as the (c) polyalkenoic acid.

[0041] Specific examples of ethylenically unsaturated monomers having an acidic group that can be used to obtain the (c) polyolefinic acid include ethylenically unsaturated monocarboxylic acids such as (meth)acrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, and 2-cyanoacrylic acid; ethylenically unsaturated dicarboxylic acids such as mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, and citraconic acid; ethylenically unsaturated tricarboxylic acids such as aconitic acid, 1-butene-1,2,4-tricarboxylic acid, and 3-butene-1,2,3-tricarboxylic acid; 2-(meth)acryloyloxyethyl phosphoric acid, 2-(meth)acryloyloxyethylphenyl phosphoric acid, 2-(meth)acryloyloxyethylphenyl-2-bromoethyl phosphoric acid, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 12- Ethylenically unsaturated phosphoric acids such as (meth)acryloyloxydodecyl dihydrogen phosphate, ethylenically unsaturated phosphonic acids such as 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, and 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and ethylenically unsaturated sulfonic acids such as vinyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, methallylsulfonic acid, methallyloxybenzenesulfonic acid, allyloxybenzenesulfonic acid, and styrenesulfonic acid may be used, but are not limited thereto.

[0042] The polymerization method for obtaining various (c) polyolefinic acids is not particularly limited, and substances polymerized by any method such as solution polymerization, suspension polymerization, emulsion polymerization, etc. can be used without any restriction. In addition, the polymerization initiator and chain transfer agent used in the synthesis of the polymer can use known substances, and their addition amounts can be appropriately adjusted to obtain the desired polymer. The (c) polyolefinic acids obtained in this way can be used alone or in combination of multiple types.

[0043] The weight average molecular weight of the (c) polyolefinic acid is preferably in the range of 3000 or more and 300000 or less. Here, the weight average molecular weight refers to the average molecular weight calculated based on the molecular weight distribution measured by gel permeation chromatography. If the weight average molecular weight of the (c) polyolefinic acid is less than 3000, there is a case where the removability of the remaining cement is reduced, the bonding strength is reduced, or the mechanical properties are reduced. In addition, if the weight average molecular weight of the (c) polyolefinic acid is greater than 300000, sometimes the removability of the remaining cement is reduced, the operating margin time becomes shorter, or the viscosity of the kneaded product becomes higher and the kneading property becomes worse, a uniform kneaded product cannot be obtained, and the mechanical properties are reduced. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain only the (c) polyolefinic acid having a weight average molecular weight in the range of 3000 or more and 300000 or less as the (c) polyolefinic acid.

[0044] In addition, as long as (c) polyolefin acid is within the range that does not have adverse effects on various properties, it can be used with a basic compound to neutralize a part of the acidic groups for the purpose of adjusting the acid-base reactivity with (b) acid-reactive glass powder. As the basic compound used for neutralization, hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, lithium hydroxide, or carbonates of alkali metals such as sodium carbonate, potassium carbonate, lithium carbonate, or bicarbonates of alkali metals such as sodium bicarbonate, potassium bicarbonate, lithium bicarbonate. In addition, as long as it is within the range that can maintain solubility in water after neutralization, there is no problem in using various amine compounds such as primary amines, secondary amines and tertiary amines. As amine compounds, triethanolamine, diethanolamine, methyldiethanolamine, 2-dimethylaminoethyl (methyl) acrylate, etc. are preferably used.

[0045] The content of (c) polyolefinic acid contained in the second agent is required to be in the range of greater than 20% by mass and less than 70% by mass, preferably greater than 25% by mass and less than 65% by mass, relative to the total amount of the second agent of the dental adhesive resin-reinforced glass ionomer cement composition of the present invention. If the content of (c) polyolefinic acid is 20% by mass or less, the adhesion to tooth structure and the removability of the remaining cement are reduced. In addition, if the content of (c) polyolefinic acid is 70% by mass or more, the adhesion to tooth structure is reduced.

[0046] In addition, when the total amount of (c) polyolefinic acid contained in the second agent of the dental adhesive resin reinforced glass ionomer cement composition of the present invention and (d) water contained in the second agent described later is set to 100 mass%, the content of (c) polyolefinic acid contained in the second agent is required to be in the range of greater than 45 mass% and less than 75 mass%, preferably greater than 50 mass% and less than 75 mass%, and more preferably greater than 52.5 mass% and less than 75 mass%. If the content of (c) polyolefinic acid is 45 mass% or less, the adhesion to tooth structure and the removability of excess cement are reduced. In addition, if the content of (c) polyolefinic acid is 75 mass% or more, the adhesion to tooth structure and the removability of excess cement are reduced.

[0047] The (d) water that can be used in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention functions as a solvent for dissolving the (c) polyolefinic acid and is a component for diffusing the metal ions dissolved from the (b) acid-reactive glass powder and causing a crosslinking reaction with the (c) polyolefinic acid.

[0048] (d) Water may be used without any limitation as long as it does not contain impurities that inhibit the acid-base reaction in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention or adversely affect the curability or mechanical properties. Distilled water or ion-exchanged water is preferably used.

[0049] The content of (d) water is preferably 6% by mass or more and 50% by mass or less relative to the total amount of the dental adhesive resin-reinforced glass ionomer cement composition of the present invention. If the content of (d) water is less than 6% by mass or the content of (d) water is greater than 50% by mass, the curability may be reduced or the mechanical properties may be reduced.

[0050] The molecular structure of the (e) polymerizable monomer that can be used in the dental adhesive resin reinforced glass ionomer cement composition of the present invention is not particularly limited, and known polymerizable monomers can be used. That is, as the polymerizable unsaturated group possessed by the (e) polymerizable monomer, (meth) acryloyloxy, (meth) acrylamide, styrene, vinyl, allyl, etc. can be cited, but are not limited to these. Among these polymerizable unsaturated groups, (meth) acryloyloxy or (meth) acrylamide is preferred due to the excellent polymerization rate. In addition, the number of polymerizable unsaturated groups possessed by the (e) polymerizable monomer is not particularly limited. For the hydrocarbon group bonded to the polymerizable unsaturated group, it can be any one of an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a combination thereof, and further, the hydrocarbon group can have any substituents such as an acidic group, a hydroxyl group, a halogen atom, an alkoxy group, an amino group, a glycidyl group, etc. In the following, (e) polymerizable monomers are specifically exemplified, but are not limited to these. In addition, they can be used alone or in combination of two or more.

[0051] Examples of the monofunctional polymerizable monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, adamantyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, isobornyl (meth)acrylate, allyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and (meth)acrylate. (Meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glyceryl (meth)acrylate, methyl (meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl propionate, acetoacetoxyethyl (meth)acrylate, acetoacetoxypropyl (meth)acrylate, acetoacetoxybutyl (meth)acrylate, γ-(meth)acryloyloxy Silane compounds such as propyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, amines such as 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2-(N,N-diethylamino)ethyl (meth)acrylate, fluorine-containing (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, perfluorohexylethyl (meth)acrylate, and perfluorooctylethyl (meth)acrylate, and their (meth)acrylamides, and N-hydroxymethyl (meth)acrylamide, etc.

[0052] Examples of the aromatic bifunctional polymerizable monomer include 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2(4-(meth)acryloyloxyethoxyphenyl)-2(4 -(meth)acryloxydiethoxyphenyl)propane, 2(4-(meth)acryloxydiethoxyphenyl)-2(4-(meth)acryloxytriethoxyphenyl)propane, 2(4-(meth)acryloxydipropoxyphenyl)-2(4-(meth)acryloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane, 9,9-bis[4-(2-(meth)acryloxyethoxy)phenyl]fluorene, and (meth)acrylamide thereof, etc.

[0053] Examples of the aliphatic bifunctional polymerizable monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate. (meth)acrylate, 1,10-decanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 2-hydroxypropyl-1,3-di(meth)acrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, 2-hydroxy-3-acryloxypropyl (meth)acrylate, 1,2-bis(3-(meth)acryloxy-2-hydroxypropoxy)ethane, 1,2-bis(3-(meth)acryloxy-2-hydroxypropoxy)propane, 2-hydroxy-1,3-bis(3-(meth)acryloxy-2-hydroxypropoxy)propane, and (meth)acrylamide thereof, etc.

[0054] Examples of trifunctional or higher-functional polymerizable monomers include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and (meth)acrylamides thereof.

[0055] Examples of the urethane polymerizable monomer include (meth)acrylate compounds having a urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, and an isocyanate compound such as methylcyclohexane diisocyanate, methylenebis(4-cyclohexyl isocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methyl methylbenzene, and 4,4-diphenylmethane diisocyanate.

[0056] In addition, the (e) polymerizable monomer is preferably contained in an amount of 1% by mass or more and 70% by mass or less, and more preferably 2.5% by mass or more and 60% by mass or less, relative to the total amount of the dental adhesive resin-reinforced glass ionomer cement composition of the present invention. If the content of the (e) polymerizable monomer is less than 1% by mass or the content of the (e) polymerizable monomer is greater than 70% by mass, the curability may be reduced or the mechanical properties may be reduced.

[0057] Furthermore, it is preferred that the (e) polymerizable monomer contain a water-soluble polymerizable monomer. When a water-soluble polymerizable monomer is contained, the wettability of the composition to tooth structure is improved, and the adhesiveness to tooth structure is sometimes improved.

[0058] In the present invention, the water-soluble polymerizable monomer refers to a compound having a solubility of 5 parts by mass or more in 100 g of water at 25° C. and having at least one polymerizable unsaturated group. As the water-soluble polymerizable monomer, a monomer having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, and an amide group is preferred.

[0059] Specific examples of water-soluble polymerizable monomers include (meth)acrylic acid, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-((meth)acryloyloxy)ethyltrimethylammonium chloride, 3-chloro-2-hydroxypropyl (meth)acrylate, polyethylene glycol di(meth)acrylate (containing 9 or more ethyleneoxy groups), 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, 1,3-dimethacrylic acid glyceryl. Oil esters, N-hydroxymethyl (meth) acrylamide, N-hydroxyethyl (meth) acrylamide, N, N-bis (2-hydroxyethyl) (meth) acrylamide, N-methoxymethyl (meth) acrylamide, N-ethoxymethyl (meth) acrylamide, diacetone (meth) acrylamide, 4- (meth) acryloyl morpholine, N-trihydroxymethyl-N-methyl (meth) acrylamide, N, N-bis (2-acrylamidoethyl) acrylamide, N, N'-1, 2-ethanediylbis {N- [2- (acryloylamino) ethyl] acrylamide}, N- [tris (3-acrylamidopropoxymethyl) methyl] acrylamide, etc., but are not limited to these. In addition, these can be used alone or in combination of two or more.

[0060] The water-soluble polymerizable monomer preferably contains 10% by mass or more and 97.5% by mass or less, and more preferably contains 20% by mass or more and 95% by mass or less, relative to the total amount of the polymerizable monomer (e). If the content of the water-soluble polymerizable monomer is less than 10% by mass, the effect of improving the adhesion to the tooth structure may not be fully obtained. In addition, if the content of the water-soluble polymerizable monomer is greater than 97.5% by mass, the mechanical properties may be reduced.

[0061] The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain (f) an acidic component with a molecular weight of 500 or less, so as to maintain a semi-cured state suitable for removing the remaining cement for a longer time. Here, the acidic component with a molecular weight of 500 or less (f) refers to a compound having an acidic group such as a carboxyl group, a phosphoric acid group, a phosphonic acid group, a sulfonic acid group, etc. in the molecule and having a molecular weight of 500 or less. Among these (f) acidic components with a molecular weight of 500 or less, compounds whose acidic groups are carboxyl groups are preferred, and compounds having two or more carboxyl groups are more preferred. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain only compounds whose acidic groups are carboxyl groups as (f) acidic components with a molecular weight of 500 or less, and can contain only compounds having two or more carboxyl groups as (f) acidic components with a molecular weight of 500 or less. In addition, the acidic component with a molecular weight of 500 or less (f) is further preferably a compound without a polymerizable group. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain only a compound having no polymerizable group as (f) an acidic component having a molecular weight of 500 or less.

[0062] Specific examples of (f) acidic components having a molecular weight of 500 or less include acetic acid, propionic acid, (meth)acrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, tartaric acid, mesaconic acid, itaconic acid, maleic acid, fumaric acid, glutaconic acid, citraconic acid, citric acid, malic acid, aconitic acid, tricarboxylic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, carboxylic acid compounds such as 4-(meth)acryloyloxyethyl trimellitic acid, phosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, 2-(meth)acryloyloxyethyl phosphoric acid, 2-(meth)acryloyloxyethylphenyl phosphoric acid, 10-(meth)acryloyloxydecyl diphosphate Phosphonic acid compounds such as phosphonic acid, methylphosphonic acid, 5-(meth)acryloyloxypentylphosphonopropionate, 6-(meth)acryloyloxyhexylphosphonopropionate, 10-(meth)acryloyloxydecylphosphonopropionate, 6-(meth)acryloyloxyhexylphosphonoacetate, 10-(meth)acryloyloxydecylphosphonoacetate, vinylsulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-sulfoethyl(meth)acrylate, alkylbenzenesulfonic acid, styrenesulfonic acid, but are not limited to these. In addition, these (f) acidic components with a molecular weight of 500 or less can be used alone or in combination of a plurality of them.

[0063] The (f) acidic component with a molecular weight of 500 or less is preferably contained in an amount of 0.1% by mass or more and 20% by mass or less relative to the total amount of the dental adhesive resin-reinforced glass ionomer cement composition of the present invention. If the content of the (f) acidic component with a molecular weight of 500 or less is less than 0.1% by mass, the time for maintaining the semi-cured state may not be sufficiently prolonged. In addition, if the content of the (f) acidic component with a molecular weight of 500 or less is greater than 20% by mass, the mechanical properties and the adhesion to the tooth structure may be reduced.

[0064] The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain a chemical polymerization initiator other than the (a) aryl borate compound as long as the effects of the present invention are not impaired.

[0065] Specific examples of chemical polymerization initiators other than (a) aromatic borate compounds include peroxide / amine compounds, peroxide / amine compounds / aromatic sulfinic acid or its salt, or aromatic sulfonyl compounds, peroxide / amine compounds / (thio)barbituric acid compounds or (thio)barbituric acid salt compounds, peroxide / ascorbic acid compounds, peroxide / thiourea / vanadium compounds or copper compounds, (thio)barbituric acid compounds / organometallic compounds / organohalogen compounds, aromatic sulfinic acid salts that initiate polymerization under the action of acidic compounds, or a system of a combination of (thio)barbituric acid salts and acidic compounds, and organic boron compounds that further react with oxygen or water to initiate polymerization, but are not limited to these.

[0066] Examples of the peroxide include sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium peroxodiphosphate, potassium peroxodiphosphate, ammonium peroxodiphosphate, diacyl peroxides, alkyl peroxyesters, peroxydicarbonates, monoperoxycarbonates, peroxyketals, dialkyl peroxides, hydroperoxides, and ketone peroxides. More specifically, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, diacetyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, tert-amyl hydroperoxide, isopropylbenzene hydroperoxide, 5-phenyl-4-pentenyl hydroperoxide, tert-butyl peroxyisopropyl carbonate, methyl ethyl ketone peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, tert-butyl peroxybenzoate and the like can be cited, but the present invention is not limited thereto.

[0067] As the amine compound, an aromatic secondary amine or an aromatic tertiary amine is preferred. Specific examples include N-methyl-p-toluidine, N-ethyl-p-toluidine, N-(2-hydroxyethyl)-p-toluidine, ethyl p-methylaminobenzoate, N-methylaniline, N-ethylaniline, N-(2-hydroxyethyl)aniline, N,N-dimethylaniline, N,N-diethylaniline, N,N-bis(2-hydroxyethyl)aniline, N-(2-hydroxyethyl)-N-methylaniline, N-ethyl-N-(2-hydroxyethyl)aniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl p-dimethylaminobenzoate, etc., but are not limited to these.

[0068] Examples of the aromatic sulfinic acid or its salt or aromatic sulfonyl compound include benzenesulfinic acid, p-toluenesulfinic acid, o-toluenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and sodium salts, potassium salts, lithium salts or ammonium salts thereof, benzenesulfonyl chloride, benzenesulfonyl fluoride, benzenesulfonamide, benzenesulfonyl hydrazide, p-toluenesulfonyl chloride, p-toluenesulfonyl fluoride, p-toluenesulfonamide, p-toluenesulfonyl hydrazide, but are not limited thereto.

[0069] Examples of the (thio)barbituric acid compound or (thio)barbiturate compound include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 5-laurylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5- Isobutylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-phenyl-5-benzylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, thiobarbituric acid, 1,3-dimethylthiobarbituric acid, 5-phenylthiobarbituric acid, and alkali metal salts (lithium, sodium, potassium salts, etc.), alkaline earth metal salts (calcium, strontium, barium salts, etc.), ammonium salts, tetramethylammonium salts or tetraethylammonium salts thereof, but are not limited thereto.

[0070] Examples of the ascorbic acid compound include, but are not limited to, L(+)-ascorbic acid, erythorbic acid, sodium L(+)-ascorbate, potassium L(+)-ascorbate, calcium L(+)-ascorbate, sodium erythorbate and the like.

[0071] Examples of the thiourea compound include, but are not limited to, 1,3-dimethylthiourea, tetramethylthiourea, 1,1-diethylthiourea, 1,1,3,3-tetraethylthiourea, 1-allyl-2-thiourea, 1,3-diallylthiourea, 1,3-dibutylthiourea, 1,3-diphenyl-2-thiourea, 1,3-dicyclohexylthiourea, ethylenethiourea, N-methylthiourea, N-phenylthiourea, N-benzoylthiourea, and N-acetylthiourea.

[0072] Examples of the vanadium compound include vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, and vanadium benzoylacetonate, but the vanadium compound is not limited thereto.

[0073] Examples of the copper compound include copper acetate, copper salicylate, copper gluconate, copper oleate, copper benzoate, copper acetylacetonate, and copper naphthenate, but are not limited thereto.

[0074] Examples of the organometallic compound include, in addition to the aforementioned copper compounds, manganese acetylacetonate, manganese naphthenate, manganese octoate, cobalt acetylacetonate, cobalt naphthenate, lithium acetylacetonate, lithium acetate, zinc acetylacetonate, zinc naphthenate, nickel acetylacetonate, nickel acetate, aluminum acetylacetonate, calcium acetylacetonate, iron acetylacetonate, chromium acetylacetonate, sodium naphthenate, and the like, but are not limited thereto.

[0075] Examples of the organic halogen compound include tetramethylammonium chloride, tetraethylammonium chloride, trioctylmethylammonium chloride, dilauryldimethylammonium chloride, lauryldimethylbenzylammonium chloride, tetra-n-butylammonium chloride, benzyldimethylhexadecylammonium chloride, benzyldimethylstearylammonium chloride, and the like, but are not limited thereto.

[0076] As an acidic compound reacting with aromatic sulfinates or (thio) barbiturates, inorganic acids and organic acids can be used without any restrictions, preferably organic acids. Further, from the viewpoint of the stability of the solidified material, it is most preferred that organic acids use organic acids with polymerizable groups, i.e. polymerizable monomers containing acidic groups. For polymerizable monomers containing acidic groups, the types and quantities of polymerizable groups and acidic groups are not particularly limited, and substances commonly used in the dental field can be used. As acidic groups, carboxyl groups, phosphoric acid groups, phosphonic acid groups and sulfonic acid groups can be cited. As representative polymerizable monomers containing acidic groups used in the dental field, 10-(methyl) acryloyloxydecyl dihydrogen phosphate, 6-(methyl) acryloyloxyhexyl-3-phosphonoacetate, 4-(methyl) acryloyloxyethyl trimellitic acid and its anhydride, 10-(methyl) acryloyloxy-1,1-decanedicarboxylic acid, etc. can be cited, but are not limited to these. These acidic compounds may be used alone or in combination of plural.

[0077] Examples of organic boron compounds that react with oxygen or water to initiate polymerization include trialkylborons such as triethylboron, tri(n-propyl)boron, triisopropylboron, tri(n-butyl)boron, tri(sec-butyl)boron, triisobutylboron, tripentylboron, trihexylboron, tricyclohexylboron, and partial oxides thereof, but are not limited to these.

[0078] When a chemical polymerization initiator other than (a) an aryl borate compound is contained in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention, the chemical polymerization initiator is preferably contained in an amount of 0.01% by mass to 20% by mass, and more preferably in an amount of 0.1% by mass to 15% by mass, relative to the total amount of the (e) polymerizable monomer. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not contain a chemical polymerization initiator other than (a) an aryl borate compound.

[0079] A photopolymerization initiator that initiates polymerization by irradiation with ultraviolet rays or visible rays may be added to the dental adhesive resin-reinforced glass ionomer cement composition of the present invention.

[0080] Examples of the photopolymerization initiator that can be used in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention include initiators composed of photosensitizers, photosensitizer / photopolymerization accelerators, etc. Specific examples of photosensitizers include benzil, camphorquinone, α-naphthil, naphthyl acetone, p,p'-dimethoxybenzil, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, α-diketones such as naphthol, benzoin, benzoin methyl ether, benzoin ethyl ether, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, etc. Thioxanthones such as 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, benzophenone, p-chlorobenzophenone, p-methoxybenzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, Acylphosphine oxides such as methoxybenzoyl)phenylphosphine oxide, α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1, benzyl dimethyl ketal, benzyl diethyl ketal, benzyl (2-methoxyethyl ketal) and other ketals, 3-(4-methoxybenzoyl) coumarin, 3-benzoyl-5,7-dimethoxycoumarin Coumarins such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium, etc., but are not limited to these.

[0081] Specific examples of photopolymerization accelerators include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, isopentyl p-dimethylaminobenzoate, methyl N,N-dimethyl anthranilate, N,N-dihydroxyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminophenyl alcohol, and p-dimethylaminophenyl alcohol. Ethylene, N,N-dimethyl-3,5-dimethylaniline, 4-dimethylaminopyridine, N,N-dimethyl-α-naphthylamine, N,N-dimethyl-β-naphthylamine, triethanolamine, tributylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tertiary amines such as 2,2'-(n-butylimino)diethanol, secondary amines such as N-phenylglycine, 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1,3 Barbituric acids such as 1,5-trimethylbarbituric acid, 1,3,5-trimethylbarbituric acid sodium, 1,3,5-trimethylbarbituric acid calcium, 2,4,6-tris(trichloromethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenyl)-4,6-bis(trichloromethyl)-s-triazine, diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(4-methylphenyl)iodonium hexafluorophosphate , diaryl iodonium salts such as bis(4-methylphenyl)iodonium hexafluoroantimonate, bis(4-methylphenyl)iodonium tetra(pentafluorophenyl)borate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium tetra(pentafluorophenyl)borate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin ditert-carbonate, dioctyltin bis(isooctylthioacetate), tetramethyl-1,3-diacetoxydistannoxane and other tin compounds, aldehyde compounds such as lauryl aldehyde and terephthalaldehyde, sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decyl mercaptan, and thiosalicylic acid, etc., but are not limited to these.

[0082] Furthermore, in order to improve the photopolymerization promoting ability, in addition to the above-mentioned photopolymerization accelerators, adding oxocarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxoisobutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, and dihydroxymethylpropionic acid is effective, but is not limited to these.

[0083] Regardless of the polymerization method of these polymerization initiators, they can be used alone or in combination of a plurality of them. In addition, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules as required without any problem.

[0084] When a photopolymerization initiator is included in the dental adhesive resin-reinforced glass ionomer cement composition of the present invention, the photopolymerization initiator is preferably included in an amount of 0.01% by mass or more and 20% by mass or less, and more preferably 0.1% by mass or more and 15% by mass or less, relative to the total amount of the (e) polymerizable monomer. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not include a photopolymerization initiator. In addition, the dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not include a polymerization initiator other than the (a) aryl borate compound.

[0085] Furthermore, the dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain any non-acid-reactive powder for the purpose of adjusting workability, mechanical properties or curing properties within a range that does not adversely affect the properties.

[0086] As long as the non-acid reactive powder that can be used for the dental adhesive resin reinforced glass ionomer cement composition of the present invention does not contain elements that react with the acidic groups possessed by (c) polyolefinic acid, it can be used without particular limitation. As non-acid reactive powder, powders known as dental filling materials, such as inorganic filling materials, organic filling materials and organic-inorganic composite filling materials, etc. can be cited, and they can be used alone or in combination of a plurality of kinds. Among them, inorganic filling materials are particularly preferably used. In addition, the shape of these non-acid reactive powders is not particularly limited, and can be any shape such as spherical, needle-shaped, plate-shaped, broken, flaky, and further, even their agglomerates do not have any problem. The average particle size of these non-acid reactive powders is not particularly limited either, and is preferably more than 0.001 μm and less than 30 μm.

[0087] Specific examples of inorganic filling materials include quartz, amorphous silica, ultrafine silica, various glasses that do not contain elements that react with acidic groups (including glasses produced using a melting method, synthetic glasses produced using a sol-gel method, glasses produced through gas phase reactions, etc.), silicon nitride, silicon carbide, boron carbide, etc., but are not limited to these.

[0088] When the dental adhesive resin-reinforced glass ionomer cement composition of the present invention contains non-acid reactive powder, it is preferred that the non-acid reactive powder is contained in a range of 0.001 mass % to 20 mass % relative to the total amount of the composition. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not contain non-acid reactive powder.

[0089] Furthermore, when the dental adhesive resin-reinforced glass ionomer cement composition of the present invention has a paste form, a thickener may be arbitrarily contained within a range that does not adversely affect various properties in order to adjust the paste properties.

[0090] The thickener that can be used in the dental adhesive resin reinforced glass ionomer cement composition of the present invention may be any of an inorganic thickener and an organic thickener. Examples of the inorganic thickener include fumed silica, calcium carbonate, calcium silicate, magnesium silicate, saponite, montmorillonite, beidellite, vermiculite, sauconite, stevensite, hectorite, smectite, nectite, and clay minerals such as sepiolite.

[0091] Examples of the organic thickener include methylcellulose, hydroxyethylcellulose, hydroxymethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, sodium carboxymethylcellulose, calcium carboxymethylcellulose, carboxypolymethylene, sodium alginate, propylene glycol alginate, sodium polyacrylate, starch, sodium starch glycolate, starch phosphate, polyvinyl pyrrolidone, carboxyvinyl polymer, khaya gum, gum arabic, karaya gum, guar gum, etc. These can be used alone or in combination of two or more.

[0092] When the dental adhesive resin-reinforced glass ionomer cement composition of the present invention contains a thickener, the thickener is preferably contained in the paste in an amount of 0.001 mass % to 10 mass %. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may not contain a thickener.

[0093] As required, the dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain any surfactant, preservative, antibacterial material, colorant, fluorescent agent, inorganic fiber material, organic fiber material, other conventionally known additives and other components. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may be composed of a first agent and a second agent, wherein the first agent contains (a) an aryl borate compound and (b) an acid-reactive glass powder, and the second agent contains (c) a polyolefinic acid and (d) water, and at least one of the first agent and the second agent may contain only (e) a polymerizable monomer and one or more of the components specifically described in the present specification. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain only: a powder material containing (a) an aryl borate compound and (b) an acid-reactive glass powder; (c) a polyolefinic acid; (d) water; (e) a polymerizable monomer; and (f) an acidic component having a molecular weight of 500 or less. The dental adhesive resin-reinforced glass ionomer cement composition of the present invention may contain only: a powder material containing (a) an aryl borate compound and (b) an acid-reactive glass powder; (c) a polyolefinic acid; (d) water; (e) a polymerizable monomer; (f) an acidic component having a molecular weight of 500 or less; and one or more of the components specifically described in the present specification.

[0094] The dental adhesive resin-reinforced glass ionomer cement composition of the present invention can be provided in any form such as powder material / liquid material, paste / liquid material, paste / paste, etc., when (a) the aryl borate compound and / or (b) the acid-reactive glass powder and (c) the polyolefinic acid and / or (f) the acidic component having a molecular weight of 500 or less do not coexist in the presence of (d) water.

[0095] As the form of powder material / liquid material, there can be cited a combination of a powder material comprising (a) an aromatic borate compound and (b) an acid-reactive glass powder and a liquid material comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; a combination of a powder material comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder, and (f) a liquid material comprising (c) a polyolefinic acid, (d) water, and (e) a polymerizable monomer; and a combination of a powder material comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder, and (f) an acidic component having a molecular weight of 500 or less and a liquid material comprising (c) a polyolefinic acid, (d) water, and (e) a polymerizable monomer. The invention also includes but is not limited to a combination of a powder material comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder, (c) a polyolefinic acid and (f) an acidic component having a molecular weight of less than 500, and a liquid material comprising (c) a polyolefinic acid, (d) water and (e) a polymerizable monomer; a combination of a powder material comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (c) a polyolefinic acid and a liquid material comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer and (f) an acidic component having a molecular weight of less than 500, etc.

[0096] As the form of the paste / liquid material, there can be cited a combination of a paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (e) a polymerizable monomer, and a liquid material comprising (c) a polyolefinic acid, (d) water and (f) an acidic component having a molecular weight of 500 or less; a combination of a paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (e) a polymerizable monomer, and a liquid material comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer and (f) an acidic component having a molecular weight of 500 or less; a combination of a paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (d) water, and a liquid material comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer and (f) an acidic component having a molecular weight of 500 or less. The invention also includes the following embodiments of the present invention: a combination of a paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer, and a liquid material comprising (c) a polyolefinic acid, (d) water, and (f) an acidic component having a molecular weight of less than 500; a combination of a paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer, and a liquid material comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer, and a liquid material comprising (f) an acidic component having a molecular weight of less than 500; the invention also includes the following embodiments of the present invention:

[0097] As the form of paste / paste, there can be cited a combination of a first paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (e) a polymerizable monomer and a second paste comprising (c) a polyolefinic acid, (d) water and (f) an acidic component having a molecular weight of 500 or less; a combination of a first paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (e) a polymerizable monomer and a second paste comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer and (f) an acidic component having a molecular weight of 500 or less; a combination of a first paste comprising (a) an aromatic borate compound, (b) an acid-reactive glass powder and (d) water and a second paste comprising (c) a polyolefinic acid, (d) water, (e) a polymerizable monomer and a second paste comprising (f) an acidic component having a molecular weight of 500 or less. The invention also provides a combination of (a) an aromatic borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer, and (f) a second paste containing an acidic component with a molecular weight of less than 500; a combination of a first paste containing (a) an aromatic borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer, and a second paste containing (c) polyolefinic acid, (d) water, and (f) an acidic component with a molecular weight of less than 500; a combination of a first paste containing (a) an aromatic borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer, and a second paste containing (c) polyolefinic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component with a molecular weight of less than 500, etc., but is not limited to these.

[0098] Example

[0099] The present invention will be described in detail below by way of examples, but the present invention is not limited to these examples. Components (a) to (f) and other components used to prepare the dental adhesive resin-reinforced glass ionomer cement compositions of Examples and Comparative Examples and their abbreviations are as follows.

[0100] [(a) Aryl borate compound]

[0101] <Aryl borate compound having four aromatic groups in one molecule>

[0102] TPBNa: sodium tetraphenylborate.

[0103] TPBK: potassium tetraphenylborate.

[0104] <Aryl borate compound having three aromatic groups in one molecule>

[0105] BTPB: 1,2-dicyclohexyl 4,4,5,5-tetramethylbiguanide n-butyltriphenylborate.

[0106] [(b) Acid-reactive glass powder]

[0107] CK-Si-1: silane-treated aluminofluorosilicate glass powder 1 (50% particle size: 0.7 μm).

[0108] CK-Si-2: silane-treated aluminofluorosilicate glass powder 2 (50% particle size: 2.3 μm).

[0109] [(c) Polyolefinic acid]

[0110] <Polyolefinic acid having a carboxyl group>

[0111] PCA1: acrylic acid homopolymer powder (weight average molecular weight: 30,000).

[0112] PCA2: acrylic acid-3-butene-1,2,3-tricarboxylic acid copolymer powder (weight average molecular weight: 80,000).

[0113] PCA3: acrylic acid homopolymer powder (weight average molecular weight: 1000).

[0114] PCA4: acrylic acid homopolymer powder (weight average molecular weight: 350,000).

[0115] <Polyolefinic acid without carboxyl group>

[0116] PVSA: polyvinyl sulfonic acid powder (weight average molecular weight: 10,000).

[0117] [(d) Water]

[0118] Distilled water.

[0119] [(e) Polymerizable monomer]

[0120] Bis-GMA: 2,2-bis[4-[3-methacryloyloxy-2-hydroxypropoxy]phenyl]propane.

[0121] UDMA: urethane dimethacrylate.

[0122] 3G: triethylene glycol dimethacrylate.

[0123] HEMA: 2-hydroxyethyl methacrylate.

[0124] GDMA: 1,3-glycerol dimethacrylate.

[0125] FOM-03006: N-[tris(3-acrylamidopropoxymethyl)methyl]acrylamide.

[0126] [(f) Acidic component having a molecular weight of 500 or less]

[0127] <Acidic component having two or more carboxyl groups and no polymerizable group>

[0128] tartaric acid.

[0129] Citric acid.

[0130] Malic acid.

[0131] <Acidic component having one carboxyl group and no polymerizable group>

[0132] Propionic acid.

[0133] <Acidic component having two or more carboxyl groups and a polymerizable group>

[0134] 4-AET: 4-acryloyloxyethyl trimellitic acid.

[0135] <Acidic component having no carboxyl group and having a polymerizable group>

[0136] 10-MDP: 10-methacryloyloxydecyl dihydrogen phosphate.

[0137] [other]

[0138] BPO: Benzoyl peroxide.

[0139] KPS: Potassium peroxodisulfate.

[0140] DMBE: ethyl p-dimethylaminobenzoate.

[0141] AA: Ascorbic acid.

[0142] p-TSNa: sodium p-toluenesulfinate.

[0143] Aerosil R711: fumed silica (average primary particle size: about 12 nm).

[0144] Aerosil R8200: fumed silica (average primary particle size: about 12 nm).

[0145] Aerosil #200: fumed silica (average primary particle size: about 12 nm).

[0146] The method for producing the silane-treated aluminofluorosilicate glass powders 1 and 2 is as follows.

[0147] [Preparation of Aluminofluorosilicate Glass Powder 1]

[0148] After mixing various raw materials of silicon dioxide, aluminum oxide, aluminum phosphate, sodium fluoride, and strontium carbonate (glass composition: SiO2 is 26.4 weight%; Al2O3 is 29.3 weight%; SrO is 20.5 weight%; P2O5 is 10.9 weight%; Na2O is 2.5 weight% and F is 10.4 weight%), the raw material mixture is melted in a melting furnace at 1600°C. The molten liquid is taken out from the melting furnace and quenched in water to obtain glass. The obtained glass is crushed until the 50% particle size becomes 0.7 μm to obtain aluminofluorosilicate glass powder 1. It should be noted that the 50% particle size is measured by a laser diffraction particle size measuring machine (Microtrac MT3300EXII: manufactured by Nikkiso Co., Ltd., Japan).

[0149] [Preparation of Aluminofluorosilicate Glass Powder 2]

[0150] After mixing various raw materials of silicon dioxide, aluminum oxide, aluminum phosphate, sodium fluoride, and strontium carbonate (glass composition: SiO2 is 27.0 weight%, Al2O3 is 32.5 weight%, SrO is 12.8 weight%, P2O5 is 10.4 weight%, Na2O is 4.5 weight%, and F is 12.8 weight%), the raw material mixture is melted at 1600°C in a melting furnace. The molten liquid is taken out from the melting furnace and quenched in water to obtain glass. The obtained glass is crushed until the 50% particle size becomes 2.3 μm to obtain aluminofluorosilicate glass powder 2. It should be noted that the 50% particle size is measured by a laser diffraction particle size measuring machine (Microtrac MT3300EXII: manufactured by Nikkiso Co., Ltd., Japan).

[0151] [Silane treatment of aluminofluorosilicate glass powders 1 and 2]

[0152] After dispersing 200 g of aluminofluorosilicate glass powder 1 or 2 in 500 ml of water, 2 g of 3-methacryloxypropyltrimethoxysilane was added and stirred at room temperature for 2 hours. After removing the solvent, the mixture was dried at 100° C. for 5 hours to obtain silane-treated aluminofluorosilicate glass powders 1 and 2 (CK-Si-1 and 2).

[0153] [Preparation of paste]

[0154] The components were mixed at the ratios shown in Tables 1 to 3 to prepare the first preparation (paste) and the second preparation (paste) of the dental adhesive resin-reinforced glass ionomer cement composition of Examples and Comparative Examples.

[0155] [Preparation of powder materials and liquid materials]

[0156] The components were mixed at the ratios shown in Tables 4 to 6 to prepare the first agent (powder material) and the second agent (liquid material) of the dental adhesive resin-reinforced glass ionomer cement composition of Examples and Comparative Examples.

[0157] Composition (mass %) of the first agent (paste) used in Examples and Comparative Examples.

[0158] Table 1

[0159]

[0160] Composition (mass %) of the second agent (paste) used in Examples and Comparative Examples.

[0161] Table 2

[0162]

[0163] Composition (mass %) of the second agent (paste) used in Examples and Comparative Examples.

[0164] Table 3

[0165]

[0166] Composition (mass %) of the first agent (powder material) used in Examples and Comparative Examples.

[0167] Table 4

[0168]

[0169] Composition (mass %) of the second agent (liquid material) used in Examples and Comparative Examples.

[0170] Table 5

[0171]

[0172] Composition (mass %) of the second agent (liquid material) used in Examples and Comparative Examples.

[0173] Table 6

[0174]

[0175] The dental adhesive resin-reinforced glass ionomer cement compositions (Examples 1 to 66 and Comparative Examples 1 to 30) prepared by kneading the first agent and the second agent in the combination and mass ratio shown in Tables 7 to 10 were evaluated for residual cement removability and tensile bond strength. The evaluation method is as follows.

[0176] [Evaluation of the removability of residual cement]

[0177] The first and second agents of the dental adhesive resin-reinforced glass ionomer cement compositions of the examples or comparative examples were kneaded in the form of paste / paste for 20 seconds and in the form of powder / liquid for 30 seconds according to the ratios described in Tables 7 to 10, and 0.3 g of the kneaded product was applied to the center of the upper surface of a resin block (length 12×width 16×height 10 mm). The kneaded product was strongly pressed vertically to the kneaded product application surface in a manner that the sides of the same length overlapped, so that the kneaded product overflowed from between the resin blocks. Then, the kneaded product was allowed to stand at 23° C., and the kneaded product overflowed from between the resin blocks was removed as excess cement using an instrument (fine) (MiCD instrument #2 (diameter of the front end φ 0.3 mm, manufactured by Matsukaze Co., Ltd.)) or an instrument (coarse) (MiCD instrument #4 (diameter of the front end φ 1.5 mm, manufactured by Matsukaze Co., Ltd.)) 2 minutes, 3 minutes, and 4 minutes after the start of kneading, and the excess cement removal was evaluated according to the following evaluation criteria. It should be noted that when the evaluation result is A or B, it is judged to be a semi-cured state suitable for removing the remaining cement. In addition, when the evaluation results are A or B continuously after 2 minutes, 3 minutes, and 4 minutes after the start of kneading (when the evaluation results after 2 minutes and 3 minutes, 3 minutes and 4 minutes, or after 2 minutes, 3 minutes, and 4 minutes are a combination of A and A, a combination of A and B, a combination of B and A, and a combination of B and B), it is judged to have good remaining cement removal properties. For such a combination of continuous evaluations, A is set to 2 points and B is set to 1 point. As the total score increases, it is judged to show a more excellent remaining cement removal property.

[0178] [Evaluation criteria]

[0179] A: The remaining cement was in a semi-cured state and could be easily removed in one piece using an instrument (thin) (MiCD instrument #2, diameter of the tip φ0.3 mm).

[0180] B: The remaining cement was in a semi-cured state. When using the instrument (fine) (MiCD instrument #2, the diameter of the front end was φ0.3 mm), the remaining cement was torn and could not be removed in one piece. However, when using the instrument (coarse) (MiCD instrument #4, the diameter of the front end was φ1.5 mm), it could be easily removed in one piece.

[0181] C: The remaining cement was in a semi-cured state but was easily torn, and the remaining cement could not be easily removed in one piece using an instrument (coarse) (MiCD instrument #4, diameter of the front end φ1.5 mm), but the remaining cement could be removed.

[0182] D: The remaining cement is solidified and it is difficult to remove the remaining cement even with an instrument (coarse) (MiCD instrument #4, diameter of the front end φ1.5 mm).

[0183] E: The remaining cement is not cured, and it is difficult to remove the remaining cement using an instrument (coarse) (MiCD instrument #4, diameter of the front end φ1.5 mm).

[0184] [Tensile bond strength test]

[0185] The test piece made of bovine front teeth embedded with epoxy resin was ground with water-resistant abrasive paper #600 to expose the enamel plane. On the other hand, the adhered surface of a cylindrical stainless steel rod (φ4.5mm) was sandblasted (0.2MPa) with aluminum oxide particles (average particle size 50μm), washed with water and dried. The first agent and the second agent corresponding to the resin-reinforced glass ionomer cement composition for dental bonding of the embodiment or comparative example were kneaded in the form of paste / paste for 20 seconds and in the form of powder / liquid for 30 seconds according to the ratios described in Tables 7 to 10, and then an appropriate amount of the kneaded product was applied to the adhered surface of the stainless steel rod and crimped to the ground enamel plane. After removing the remaining cement under a load of 10N from the upper surface of the stainless steel rod, it was cured for 5 minutes at 37°C and a humidity of more than 90%. After curing, the 10N load was removed, and the mixture was left to stand for 1 hour at 37°C and a humidity of 90% or more, and then immersed in 37°C water for 24 hours to prepare a bonding test body. The tensile bonding strength of the prepared bonding test body was measured using a universal testing machine (manufactured by Instron) at a crosshead speed of 0.75 mm / sec.

[0186] [Evaluation criteria]

[0187] When the bonding strength was 6 MPa or more, it was determined to be excellent enough to be fully used.

[0188] When the bonding strength was 4 MPa or more and less than 6 MPa, it was determined to be usable.

[0189] When the bonding strength is less than 4 MPa, it is judged to be unsuitable for use.

[0190] Evaluation results

[0191] Table 7

[0192]

[0193] Evaluation results

[0194] Table 8

[0195]

[0196] Evaluation results

[0197] Table 9

[0198]

[0199] Evaluation results

[0200] Table 10

[0201]

[0202] <Examples 1 to 66>

[0203] Examples 1 to 66 have good excess cement removability and also exhibit excellent adhesion to tooth structure that can be fully used, and have desirable properties as a dental adhesive resin-reinforced glass ionomer cement.

[0204] <Comparative Examples 1 to 3>

[0205] In the second agents used in Comparative Examples 1 to 3, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was large. Comparative Example 1 was evaluated and it was confirmed that the adhesiveness to the tooth structure was low. In addition, Comparative Examples 2 and 3 were evaluated and it was confirmed that the removability of the remaining cement was poor and the adhesiveness to the tooth structure was also low.

[0206] <Comparative Examples 4 to 6>

[0207] The second agent used in Comparative Examples 4 to 6 contained a large amount of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was also large. Comparative Examples 4 to 6 were evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0208] <Comparative Examples 7 to 9>

[0209] The second agent used in Comparative Examples 7 to 9 had a small content of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was also small. Comparative Examples 7 to 9 were evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0210] <Comparative Examples 10 to 12>

[0211] The second agent used in Comparative Examples 10 to 12 has a low content of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent is also small. On the other hand, the first agent used in Comparative Examples 10 to 12 contains (c) polyolefinic acid, which makes up for the deficiency of (c) polyolefinic acid in the second agent. However, the evaluation of Comparative Examples 10 to 12 confirmed that the removability of the remaining cement was poor and the adhesion to the tooth structure was also low.

[0212] <Comparative Examples 13 and 14>

[0213] The second agent used in Comparative Examples 13 and 14 contained a large amount of (c) polyolefinic acid. Comparative Examples 13 and 14 were evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0214] <Comparative Examples 15 and 16>

[0215] The second agent used in Comparative Examples 15 and 16 had a small content of (c) polyolefinic acid. Comparative Examples 15 and 16 were evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0216] <Comparative Examples 17 and 18>

[0217] In the second agent used in Comparative Examples 17 and 18, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was small. Comparative Examples 17 and 18 were evaluated, and it was confirmed that the residual cement removal property was poor and the adhesion to the tooth structure was also low.

[0218] <Comparative Example 19>

[0219] Comparative Example 19 did not contain (a) the aryl borate compound, but contained AA and DMBE as other chemical polymerization initiators. Comparative Example 19 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0220] <Comparative Example 20>

[0221] Comparative Example 20 did not contain (a) the aryl borate compound, but contained BPO, AA, and DMBE as other chemical polymerization initiators. Comparative Example 20 was evaluated, and it was confirmed that the residual cement removability was poor.

[0222] <Comparative Example 21>

[0223] Comparative Example 21 did not contain (a) the aryl borate compound, but contained p-TSNa as another chemical polymerization initiator. Comparative Example 21 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0224] <Comparative Example 22>

[0225] In the second agent used in Comparative Example 22, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was large. Evaluation of Comparative Example 22 revealed that the adhesiveness to tooth structure was also low.

[0226] <Comparative Example 23>

[0227] The second agent used in Comparative Example 23 contained a large amount of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was also large. Comparative Example 23 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0228] <Comparative Example 24>

[0229] The second agent used in Comparative Example 24 had a small content of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent was also small. Comparative Example 24 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0230] <Comparative Example 25>

[0231] The second agent used in Comparative Example 25 has a small content of (c) polyolefinic acid. In addition, the ratio of (c) polyolefinic acid to (d) water contained in the second agent is also small. On the other hand, the first agent used in Comparative Example 25 contains (c) polyolefinic acid, which makes up for the deficiency of (c) polyolefinic acid in the second agent. However, the evaluation of Comparative Example 25 confirmed that the residual cement removal property was poor and the adhesion to the tooth structure was also low.

[0232] <Comparative Example 26>

[0233] The second agent used in Comparative Example 26 contained a large amount of (c) polyolefinic acid. Comparative Example 26 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0234] <Comparative Example 27>

[0235] The second agent used in Comparative Example 27 had a small content of (c) polyolefinic acid. Comparative Example 27 was evaluated, and it was confirmed that the residual cement removal property was poor and the adhesiveness to the tooth structure was also low.

[0236] <Comparative Example 28>

[0237] The second agent used in Comparative Example 28 also had a small ratio of (c) polyolefinic acid to (d) water. Comparative Example 28 was evaluated to show that the residual cement removal property was poor and the adhesiveness to tooth structure was also low.

[0238] <Comparative Example 29>

[0239] Comparative Example 29 did not contain (a) the aryl borate compound, but contained BPO (1 mass %), KPS, AA, and p-TSNa as other chemical polymerization initiators. Comparative Example 29 was evaluated, and it was confirmed that the residual cement removability was poor.

[0240] <Comparative Example 30>

[0241] Comparative Example 30 did not contain (a) the aryl borate compound, but contained BPO (0.01 mass %), KPS, AA, and p-TSNa as other chemical polymerization initiators. Comparative Example 30 was evaluated, and it was confirmed that the residual cement removability was poor.

[0242] In this specification, when a constituent element of the invention is described as either the singular or the plural, or when it is described as not limited to the singular or the plural, the constituent element may be either the singular or the plural unless it can be understood from the context.

[0243] Although the present invention has been described with reference to specific embodiments, it should be understood by those skilled in the art that various changes or modifications can be made based on the contents disclosed in this specification. Therefore, it is intended that the scope of the embodiments of the present invention includes any changes or modifications.

[0244] The dental adhesive resin-reinforced glass ionomer cement composition of the present invention can exhibit excellent adhesion to tooth structure, and can maintain a semi-cured state suitable for removing excess cement for a long period of time during the curing process. Furthermore, the excess cement in the semi-cured state also has the property of being difficult to tear, and is therefore useful as a dental cement.

Claims

1. A dental adhesive resin-reinforced glass ionomer cement composition, which is composed of a first component and a second component, and at least one of the first component and the second component contains (e) a polymerizable monomer, wherein the first component contains (a) an aryl borate compound and (b) an acid-reactive glass powder, and the second component contains (c) a polyolefinic acid and (d) water, characterized in that: Relative to the total amount of the second agent, the content of the (c) polyolefinic acid contained in the second agent is in the range of greater than 20 mass % and less than 70 mass %, and, in the total amount of 100 mass parts of the (c) polyolefinic acid contained in the second agent and the (d) water contained in the second agent, the content of the (c) polyolefinic acid contained in the second agent is in the range of greater than 45 mass parts and less than 75 mass parts.

2. The dental adhesive resin-reinforced glass ionomer cement composition according to claim 1, wherein: The content of the (c) polyalkenoic acid contained in the second agent is in a range of more than 25 mass % and less than 65 mass % based on the total amount of the second agent.

3. The dental adhesive resin-reinforced glass ionomer cement composition according to claim 1 or 2, wherein: The content of the (c) polyalkenoic acid contained in the second agent is greater than 50 parts by mass and less than 75 parts by mass based on 100 parts by mass of the total amount of the (c) polyalkenoic acid contained in the second agent and the (d) water contained in the second agent.

4. The dental adhesive resin-reinforced glass ionomer cement composition according to claim 1 or 2, wherein: The content of the (c) polyalkenoic acid contained in the second agent is greater than 52.5 parts by mass and less than 75 parts by mass based on 100 parts by mass of the total amount of the (c) polyalkenoic acid contained in the second agent and the (d) water contained in the second agent.

5. The dental adhesive resin-reinforced glass ionomer cement composition according to any one of claims 1 to 4, wherein The acidic group of the (c) polyalkenoic acid is a carboxyl group.

6. The dental adhesive resin-reinforced glass ionomer cement composition according to any one of claims 1 to 5, wherein The dental adhesive resin-reinforced glass ionomer cement composition further comprises (f) an acidic component having a molecular weight of 500 or less.

7. The dental adhesive resin-reinforced glass ionomer cement composition according to claim 6, wherein: The acidic group of the (f) acidic component having a molecular weight of 500 or less is a carboxyl group.

8. The dental adhesive resin-reinforced glass ionomer cement composition according to claim 7, wherein: The (f) acidic component having a molecular weight of 500 or less has two or more carboxyl groups.

9. The dental adhesive resin-reinforced glass ionomer cement composition according to any one of claims 6 to 8, wherein The (f) acidic component having a molecular weight of 500 or less does not have a polymerizable group.

Citation Information

Patent Citations

  • Powder liquid-type dental resin-enriched glass ionomer cement

    JP2014181190A